PEMANFAATAN ZEOLIT DIAKTIFKAN DENGAN LARUTAN ASAM UNTUK PEMURNIAN BIODIESEL - Muhammad Hidayat Furqon; Agus Prasetya; Wahyu Wilopo (Master in Systems Engineering, 2013)
Utilization of zeolite activated by acid solution for biodiesel purification has been done. This research is conducted to find the mechanism of biodiesel purification from catalyst with activated zeolite, the effectiveness of the activated zeolite of various particle size, soaking time and purification temperature, the economic feasibility of biodiesel production by using this method and the more economical method by comparing the cost and performance of biodiesel purification using activated zeolite and using water and acid solution.This research has used cooking oil, methanol and sodium hydroxide to make biodiesel, sulfuric acid as activator and zeolite from Gunung Kidul which is filled into wash column with support from vacuum pump to purify biodiesel. The variable of the research is particle size of zeolite among others: 12 mesh <De< 20 mesh, 20 mesh <De< 40 mesh and 40 mesh <De< 80 mesh, soaking time 0, 15 minutes, 30 minutes, 1 hour and 2 hours, and purification temperature 27oC, 40oC and 60oC.Mechanism of activated zeolite for purifying biodiesel from catalyst has been investigated that activated zeolite is using the absorption rate where catalyst will fill the empty pores of zeolite and its cation exchange capacity where it will exchange cation in zeolite surface with cation of catalyst so that zeolite can purify the unwashed biodiesel from catalyst. Optimization of biodiesel purification using zeolite activated by acid solution method can be achieved with particle size of the zeolite 20 mesh <De< 40 mesh, 30-minute soaking time and purification temperature at 27oC. Economic analysis of the use of zeolites in the optimum condition within one year resulted Payback Period 8.68 months, Benefit Cost Ratio 1.86, Net Present Value Rp 431,173,257.44 and Return of Investment -138 % and the use of zeolite activated by acid solution more economical than the use of water and acid solution as purifying biodiesel because of cost savings can be made up to 86% of method of using water and acid solution.